Participation in the global knowledge commons : challenges and opportunities for research dissemination in developing countries - Chan, Leslie (2005)
Purpose – This paper aims to provide a review of recent trends in the open access (OA) movement, as well as to discuss the significance of those trends for information access in developing countries. Design/methodology/approach – An analysis of the recent literature was carried out, focusing on the benefits of a greater information access in developing countries. The paper also brings together the diverse experiences from the authors on OA publishing and archiving with institutions in a number of developing countries. Findings – Knowledge workers in developing countries are now getting access to scholarly and scientific publications and electronic resources at a level that is unmatched historically. This is highly significant, if developing countries are to meet the millennium development goals. The OA movement and the growing number of Open Archive Initiative-compliant institutional repositories promise to provide even greater access to resources and publications that were previously inaccessible. These low cost technology and interoperability standards are providing great opportunities for libraries and publishers in developing countries to disseminate local research and to bridge the south-north knowledge gap. Originality/value – This paper therefore provides recommendations for knowledge workers on how to actively participate in and contribute to the global knowledge commons. The results and recommendations contained in the paper should be of interest to authors, policy makers, funding agencies and information professionals in both developing and developed countries.